Disabled people's voices on sexual well-being. Issue 2 (7th February 2020) - Lee, Sally; Fenge, Lee-Ann; Collins, Bethan
Abstract: Disabled people have equal rights to positive sexual well-being including sexual citizenship; however, this may not always be experienced and support for sexual well-being is less likely to form part of services offered by professionals in health and social care services. Inspired by disabled people, phenomenological research into the experience of sexual well-being for a group of physically disabled adults was undertaken. The results show that sexual well-being is understood in several ways. The notion of sexual well-being raises issues of the physical body, connection to notions of normality and what support disabled people want from health and social care professionals. There is a clear link between sexual well-being and other aspects of physical and emotional well-being, making it an issue which needs to be proactively addressed by health and social care professionals in ways which are directed by disabled people.